2023
DOI: 10.1002/advs.202204177
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Cells Enter an Adaptive Persistence to Survive Radiotherapy and Repopulate Tumor

Abstract: Repopulation of residual tumor cells impedes curative radiotherapy, yet the mechanism is not fully understood. It is recently appreciated that cancer cells adopt a transient persistence to survive the stress of chemo‐ or targeted therapy and facilitate eventual relapse. Here, it is shown that cancer cells likewise enter a “radiation‐tolerant persister” (RTP) state to evade radiation pressure in vitro and in vivo. RTP cells are characterized by enlarged cell size with complex karyotype, activated type I interfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 81 publications
(56 reference statements)
0
5
0
Order By: Relevance
“…Moreover, CysC may be conducive to tumor cell invasion and angiogenesis by protecting matrix metalloproteinase-9 from autolysis ( Mira et al, 2004 ; Paupert et al, 2008 ). Zhao et al also reported that elevated expression of CST3, the gene encoding cystatin C, was critical for cellular polyploidization that may facilitate cancer cells to resist radiation therapy ( Zhao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CysC may be conducive to tumor cell invasion and angiogenesis by protecting matrix metalloproteinase-9 from autolysis ( Mira et al, 2004 ; Paupert et al, 2008 ). Zhao et al also reported that elevated expression of CST3, the gene encoding cystatin C, was critical for cellular polyploidization that may facilitate cancer cells to resist radiation therapy ( Zhao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, RD cells were used to establish ectopic (41)(42)(43) and orthotopic (44) xenografts. Importantly, previous chemotherapy and radiotherapy may lead to multiple changes in tumor biology, which is different from the biology of the primary tumor including genetic mutations and alterations in the DNA and changes in tumor heterogeneity (45,46). GEMM models of RMS were infrequently utilized (n = 10), which may be attributed to their technical complexity, long development times, and high cost.…”
Section: Discussionmentioning
confidence: 99%
“…formed in the absence of TME or immune cell reaction, and based on the alternating mechanism of reversible poly- and de-polyploidization mechanism to survive radiotherapy was reported by Zhao et al [ 35 ]. It is also important that a few of specific regulatory chains may modulate relationships between separate tumor cell sub-groups, and anaplastic lymphoma kinase is a protein able to make colon cancer cells to form populations with the enhanced recurrence potential [ 36 ].…”
Section: Discussionmentioning
confidence: 99%